2018
DOI: 10.1038/s41418-018-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

cIAP1 regulates the EGFR/Snai2 axis in triple-negative breast cancer cells

Abstract: Inhibitor of apoptosis (IAP) proteins constitute a family of conserved molecules that regulate both apoptosis and receptor signaling. They are often deregulated in cancer cells and represent potential targets for therapy. In our work, we investigated the effect of IAP inhibition in vivo to identify novel downstream genes expressed in an IAP-dependent manner that could contribute to cancer aggressiveness. To this end, immunocompromised mice engrafted subcutaneously with the triple-negative breast cancer MDA-MB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…We experimentally tested our hypothesis demonstrating the higher affinity for isolated BIR3 domains by 23-(SM114) and 32-(SM130) fold, respectively. Furthermore, in vitro cell-based assays revealed that both SM114 and SM130 are able to induce apoptosis in MDA-MB231 cells, like other SMs belonging to our library [16,20,34]. Finally, SMs selectivity was confirmed by the caspase-independent autodegradation of cIAPs.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We experimentally tested our hypothesis demonstrating the higher affinity for isolated BIR3 domains by 23-(SM114) and 32-(SM130) fold, respectively. Furthermore, in vitro cell-based assays revealed that both SM114 and SM130 are able to induce apoptosis in MDA-MB231 cells, like other SMs belonging to our library [16,20,34]. Finally, SMs selectivity was confirmed by the caspase-independent autodegradation of cIAPs.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, in vitro cell-based assays revealed that both SM114 and SM130 are able to induce apoptosis in MDA-MB231 cells, like other SMs belonging to our library [16,20,34]. We then synthesized two SMs, SM114 exploiting position 292 and SM130 exploiting position 309, both predicted to have higher affinity for cIAP respect to XIAP.…”
Section: Discussionmentioning
confidence: 94%
“…With the combination of SAHA and EGCG, cIAP2 expression was reduced in the MDA-MB-157 and HCC1806 cell lines when compared to SAHA alone, though EGCG administered alone was able to reduce cIAP2 expression in the MDA-MB-231 cell line. We also found that the combination was successful in reducing cIAP2 protein levels in the MCF- inhibition of cIAP1 using a second mitochondrial activator of caspases (Smac) mimetic resulted in anticancer effects through the EGFR/Snai2 axis, which reduced tumor aggressiveness (29). Smac proteins activate apoptosis through neutralizing IAP proteins.…”
Section: Discussionmentioning
confidence: 86%
“…SNAI2 (also known as Slug), a member of Snail superfamily, is one of the transcription factors of epithelial mesenchymal transition (EMT) [32]. In recent years, it has been found that SNAI2 is abnormally expressed in various kinds of malignant tumors and plays an important role in tumor progress and prognosis [33][34][35]. To investigate the role of SNAI2 in IM cells, we examined its expression level in IM tissues and BA-induced IM cells.…”
Section: Discussionmentioning
confidence: 99%